A language for CAL: 'C' where it leads. (4th August 2014) - Makinson, G.J.; Morarji, H.L.
The wide availability of Unix and the C language has made it possible to create teaching packages which can be ported very easily from one machine to another. C programs are generally accepted to be highly portable whereas other languages such as Fortran are not. At the University of Kent, teaching packages for computational mathematics have been created in C using an authoring system, KAS, devised at Kent. The software generates graphical displays in a device–independent format using a graphics program, DIGS, written in C at Heriot–Watt University. With specific device drivers the software can display results, both numerically and graphically, in colour or mono on such displays as a BBC micro, Tektonics 4010, Sigma, or any micro emulating a Tektronics terminal. The graphical output can also be sent to an advanced plotter such as a CALCOMP or BENSON plotter. Interactive access to the software can be from a standalone workstation, over a ring network, or over a wide area network such as JANET.